2011
DOI: 10.1590/s0103-50532011001000006
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of lignin from sugar cane bagasse and its modification into a high performance dispersant for pesticide formulations

Abstract: Com o objetivo de utilizar efetivamente um sub-produto de material não madeireiro, foi extraída lignina do bagaço de cana-de-açúcar via acidificação do licor negro. A lignina extraída do bagaço da cana-de-açúcar (EBL) foi modificada por oxidação, hidroximetilação e sulfonação em um lignossulfonato solúvel em água (EBL-M). O composto foi caracterizado por IR, UV, GPC e análise elementar. Os resultados mostraram que as unidades aromáticas do EBL-M foram mantidas e efetivamente sulfonadas e que a porcentagem de S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 20 publications
1
33
0
1
Order By: Relevance
“…A similar work on the stabilization of ceramic particles using anionic polymeric dispersants, it was reported that the addition of poly acrylic acid and poly ethylene glycol improved the dispersion of ceramic particles in the suspension [54]. In addition, the produced carboxymethylated lignin may also be used as a dispersant in the mining industry (ore suspensions), pesticide formulations, ceramic suspensions and cement admixture [14,17,[55][56] …”
Section: Impacts Of Ph and Concentration On Solubilitymentioning
confidence: 92%
“…A similar work on the stabilization of ceramic particles using anionic polymeric dispersants, it was reported that the addition of poly acrylic acid and poly ethylene glycol improved the dispersion of ceramic particles in the suspension [54]. In addition, the produced carboxymethylated lignin may also be used as a dispersant in the mining industry (ore suspensions), pesticide formulations, ceramic suspensions and cement admixture [14,17,[55][56] …”
Section: Impacts Of Ph and Concentration On Solubilitymentioning
confidence: 92%
“…However, despite the widespread availability, the chemical utilization of lignin fractions from kraft pulping is practiced only on a limited scale (Gilarranz et al 1998;Lora and Glasser 2002;Calvo-Flores and Dobado 2010;Li and Ge 2011). This is mainly due to their heterogeneous nature, and the lack of capable economic methods in their isolation with high purity (Chakar and Ragauskas 2004;García et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Structurally, the characterisation of lignin can be well illustrated by the work of Li and Ge [171]. These co-workers utilised the byproduct of a non-wood material for the extraction of lignin.…”
Section: Characterisation Of Ligninsmentioning
confidence: 99%
“…According to Li and Ge [171], the relative contents of moisture, ashes and pure lignin content of extracted bagasse lignin, can be measured as follows: an appropriate amount of raw EBL is weighed and placed in an oven and heated to 105 C in air. The corresponding mass loss would Table 4.…”
Section: Characterisation Of Ligninsmentioning
confidence: 99%
See 1 more Smart Citation